Graphene Oxide-Reinforced Copper Matrix Composites: Microstructural Enhancements and Tribological Performance Via Hot Pressing - Macit, Cevher Kursat; Aksakal, Bunyamin; Horlu, Merve (Springer/Plenum Publishers, 2025)
This study investigates the effects of graphene oxide (GO) reinforcement on the microstructural, mechanical, and tribological properties of copper (Cu) matrix composites produced via powder metallurgy and hot pressing. GO nanoparticles synthesized by the Hummers method were incorporated into Cu at different weight ratios (0.5, 0.75, and 1 wt %), and the composites were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). The results revealed that GO was homogeneously distributed within the Cu matrix without forming new detectable crystalline phases, and its presence led to grain refinement and improved interfacial bonding. Hardness measurements showed that the composite containing 1 wt % GO exhibited a 109.97% increase compared to pure Cu, while tribological tests under dry sliding conditions demonstrated significant enhancements in wear resistance and reductions in the coefficient of friction. Notably, the 1 wt % GO composite achieved an 82.88% reduction in wear loss and a 51.33% decrease in friction coefficient. Post-wear SEM analysis confirmed the formation of a protective tribofilm, reduced microcrack formation, and minimized wear-induced damage. These findings highlight the effectiveness of GO as a multifunctional reinforcement for the development of high-performance Cu-based composites with superior wear resistance, making them suitable candidates for applications in electrical contact systems and other tribologically demanding environments.
Keywords: Copper matrix composites; Graphene oxide; Powder metallurgy; Wear resistance; Hot pressing; Tribology